High-temperature-resistant carbon fiber electric heating felt as well as preparation method and application thereof
By applying nanocomposite inner lining layer and self-assembled outer coating on carbon fiber electrothermal felt, the problem that carbon fiber electrothermal heating elements cannot work stably in high-temperature aerobic environment is solved, and stable operation and wide application are achieved at high temperatures of 600℃.
Patent Information
- Application Number
- CN202411824535.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-12
AI Technical Summary
Carbon fiber electric heating elements cannot operate stably under high-temperature aerobic environment, and the prior art increases additional thermal resistance by isolating oxygen, limiting their application scenarios.
A high-temperature resistant carbon fiber electrothermal felt is adopted to improve the high-temperature resistance and conductivity of carbon fibers while maintaining its lightweight and flexible through the dual protection of the nanocomposite inner lining layer and the self-assembled outer coating.
The stable operation of carbon fiber electrothermal felt at a high temperature of 600℃ has been achieved, which significantly improves its application temperature limit, expands its application range in the field of electric heating, while maintaining its original lightweight, flexible and high conductive characteristics.
Smart Images

Figure CN119777148A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electric heating materials, and in particular relates to a high-temperature resistant carbon fiber electric heating felt and a preparation method and application thereof. Background Art
[0002] As a high-performance fiber material, carbon fiber is widely used in many fields due to its advantages of light weight, softness, high temperature resistance and high tensile strength. In recent years, people have found that the application of carbon fiber in the manufacture of electric heating elements can give full play to its outstanding performance advantages and show broad application prospects in the field of electric heating. Compared with traditional metal heating elements, the electrothermal conversion efficiency of carbon fiber electric heating elements can be increased by more than 20%, which greatly improves the energy utilization efficiency. Secondly, carbon fiber has excellent infrared radiation characteristics, with an infrared emissivity of up to 0.8-0.95, and can effectively emit infrared electromagnetic waves. In the low-temperature civilian field, such as electric blankets, physiotherapy devices and other application scenarios, it can provide gentle and comfortable radiant heat for the human body; in industrial production, high infrared emissivity means that carbon fiber electric heating elements can transfer more heat to the workpiece or environment in the form of radiation. Compared with heat conduction and convection heat transfer, this radiation heating method is more efficient and uniform, which is very beneficial for high-temperature processes that require precise temperature control. In addition, carbon fiber electric heating elements also have the advantages of fast response speed, which can quickly convert electrical energy into thermal energy, achieve rapid heating, greatly shorten the heating time, and improve production and use efficiency.
[0003] However, the initial oxidation temperature of carbon fiber is around 400°C. When the temperature exceeds 500°C, a violent oxidation reaction will occur, causing its mechanical strength and electrical conductivity to drop sharply, severely limiting the operating temperature range of carbon fiber electric heating elements, making it impossible to work stably in high-temperature aerobic environments. In order to solve this problem, researchers have developed carbon fiber electric heating tubes, which isolate oxygen by placing the carbon fiber heating element in a vacuum or in a quartz tube filled with inert gas. Although this method ensures that the carbon fiber electric heating element can generate heat stably under high temperature conditions, the presence of the quartz tube not only hinders heat transfer, but also sacrifices the advantages of carbon fiber itself, such as light weight and flexibility, limiting its application scenarios. Therefore, it is of great significance and practical value to develop a carbon fiber electric heating element that can work in a high-temperature aerobic environment while retaining the characteristics of light weight and flexibility and not adding additional thermal resistance.
[0004] Patent CN105645962B provides a method for preparing a high temperature resistant, oxidation resistant, and heat conductive carbon fiber / silicon carbide composite material: soaking carbon fiber fabric in Fe(NO3)3 solution, soaking and drying; placing the catalyst-loaded carbon fiber fabric in a tubular furnace; introducing Ar and H2; then introducing a carbon source, and obtaining a carbon fiber fabric with carbon nanotubes after growth; stacking 4-8 layers of carbon fiber fabric and soaking them in a xylene solution of polycarbosilane; taking out the carbon fiber fabric stack after soaking in a negative pressure state, and forming a block after drying; placing it in a muffle furnace for oxidation for 1-2 hours; placing the block in a tubular furnace, introducing Ar and heating it to 1200°C, and then cooling it to obtain a high temperature resistant, oxidation resistant, and heat conductive carbon fiber / silicon carbide composite material. However, the conductivity and flexibility of the composite material obtained by this patent are reduced to varying degrees compared with the original carbon fiber fabric. Patent CN115262218B provides a method for preparing high-temperature resistant and oxidation-resistant carbon fiber, including the process steps of carbon fiber surface treatment, atomic layer deposition of an oxidation-resistant layer, and high-temperature oxygen-free annealing, to obtain carbon fiber with a high-temperature resistant and oxidation-resistant film deposited on the surface. The high-temperature resistant and oxidation-resistant film on the surface of the carbon fiber is compounded with different components and structurally designed. Silicon atoms are preferentially deposited to form a silicon carbide interface layer between the carbon fiber and the oxidation-resistant film, and the bonding force between the two is enhanced by chemical bonds; silicon oxide layers and aluminum oxide layers are alternately stacked and deposited, and the number of aluminum oxide deposition layers changes periodically, forming a more dense and void-free membrane structure, which improves the high-temperature resistance and oxidation resistance of the carbon fiber; and the thickness of the oxidation-resistant film layer is at the nanometer and micrometer level, which ensures the softness of the carbon fiber. However, the dense coating of this patent hinders the conduction of electrons between fibers and reduces the electrical conductivity. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a high-temperature resistant carbon fiber electric heating felt and its preparation method and application. The carbon fiber electric heating felt has excellent high-temperature resistance while ensuring light weight, flexibility, good conductivity and high emissivity.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] The present invention provides a method for preparing a high temperature resistant carbon fiber electric heating felt, comprising the following steps:
[0008] S1, mixing silicon oxide, titanium oxide, silicon carbide, and titanium carbide nanopowders in a mass ratio of (0.5-2): (0.5-2): (0.5-2) to obtain a mixed nanopowder, then adding water, a coupling agent, a thickener, and a dispersant, and obtaining a nanocomposite emulsion after shearing and stirring,
[0009] In step S1, the mass ratio of water to mixed nano-powder is 1:1-3:1, the mass of coupling agent is 1-5% of the total mass of water and mixed nano-powder, the mass of thickener is 5-15% of the total mass of water and mixed nano-powder, and the mass of dispersant is 1-3% of the total mass of water and mixed nano-powder;
[0010] S2, Preparation of Carbon Fiber Felt Nanocomposite Lining Layer:
[0011] S2-1, immersing the carbon fiber felt in concentrated nitric acid at 75° C. for oxidation activation for 3 to 8 hours, washing with water and then drying to obtain activated carbon fiber felt;
[0012] S2-2, immersing the activated carbon fiber felt obtained in step S2-1 into the nanocomposite emulsion obtained in step S1, heating to 50-60° C., and ultrasonically treating for 30 min with an ultrasonic power of 50-100 W and a frequency of 20-60 kHz;
[0013] S2-3, taking out the carbon fiber felt treated in step S2-2, drying it at 60-80° C. for 1-3 hours, and then performing heat treatment, wherein the heat treatment conditions are: nitrogen atmosphere, heating rate of 3-5° C. / min, heating to 1300-1600° C., keeping the temperature for 2-3 hours, and cooling naturally;
[0014] S2-4, heating the carbon fiber felt treated in step S2-3 to 50-60° C., and ultrasonically cleaning the felt for 0.5-3 h at an ultrasonic power of 80-120 W and a frequency of 30-80 kHz to obtain a carbon fiber felt with a nano-composite lining layer coated on the fiber surface;
[0015] S3, silanization treatment of carbon fiber felt: immerse the carbon fiber felt with the nano-composite lining layer coated on the fiber surface obtained in step S2-4 in water, then add a coupling agent with a mass of 1 to 3% of the mass of water and an organic silane with a mass of 1 to 3% of the mass of water, stir well and let stand for 20 to 30 hours, take out, dry, and obtain a carbon fiber felt with silanized fiber surface;
[0016] S4, silanization treatment of the emissivity enhancing powder: fully stir water, emissivity enhancing powder, coupling agent, and organic silane in a mass ratio of 100:(5-15):(1-3):(1-3), let stand for 20-30 hours, take out, and dry to obtain silanized emissivity enhancing powder;
[0017] S5, silanization treatment of the conductive enhanced powder: fully stir water, conductive enhanced powder, coupling agent, and organic silane in a mass ratio of 100:(5-15):(1-3):(1-3), let stand for 20-30 hours, take out, and dry to obtain silanized conductive enhanced powder;
[0018] S6, preparation of silicon oxide-aluminum oxide-titania composite sol:
[0019] S6-1, uniformly mixing a silicon oxide precursor, an aluminum oxide precursor, and a titanium oxide precursor in a molar ratio of (2-3): (1-1.5): (1-1.5), and then adding anhydrous ethanol in a ratio of anhydrous ethanol volume: total precursor volume = (2:1) to (3:1), and mixing thoroughly to obtain a precursor mixed solution;
[0020] S6-2, slowly adding water dropwise to the precursor mixed solution obtained in step S6-1 while stirring, wherein the molar ratio of the total amount of the precursor to the added water is 3:1 to 4:1;
[0021] S6-3, adjusting the pH of the solution obtained in step S6-2 to 5-6 with glacial acetic acid, aging at room temperature to 60° C. for 20-30 hours to obtain a silicon oxide-aluminum oxide-titanium oxide composite sol;
[0022] S7, outer coating self-assembly step:
[0023] S7-1, dispersing the silanized emissivity enhancement powder obtained in step S4 and the silanized conductivity enhancement powder obtained in step S5 in the silicon oxide-alumina-titania composite sol obtained in step S6-3, wherein the mass ratio of the silanized emissivity enhancement powder, the silanized conductivity enhancement powder, and the silicon oxide-alumina-titania composite sol is (2-5):1:(3-10), and after sufficient stirring, adding the carbon fiber felt with silanized fiber surface obtained in step S3, and reacting for 1-3 days under slow stirring;
[0024] S7-2, during the reaction process, 5 g of 3-5 wt.% alkali metal carbonate aqueous solution was added dropwise every 6-8 hours. After the reaction was completed, the pH of the reaction system was adjusted to 8-12 with 5-20 wt.% ammonia water, and then the carbon fiber felt was taken out, rinsed with anhydrous ethanol 1-2 times, and dried at 60-80° C. for 2 hours to obtain a carbon fiber felt with a self-assembled outer layer coating on the surface;
[0025] S8, densification of the self-assembled outer layer coating: heat-treat the carbon fiber felt with the surface self-assembled outer layer coating obtained in step S7-2 under the following conditions: nitrogen atmosphere, heating to 800-1200°C at 3-10°C / min, keeping warm for 1-3h, and naturally cooling to obtain a high-temperature resistant carbon fiber electric heating felt with a double-layer coating on the fiber surface.
[0026] Furthermore, in step S1, the particle size of the silicon oxide, titanium oxide, silicon carbide, and titanium carbide nanopowders is in the range of 20 nm to 80 nm.
[0027] The silicon oxide, titanium oxide, silicon carbide and titanium carbide nanopowders are ball-milled to obtain mixed nanopowders. The ball milling speed is 200 r / min to 500 r / min and the ball milling time is 0.5 h to 3 h.
[0028] The coupling agent is selected from at least one of KH550, KH560 or KH570,
[0029] The thickener is selected from at least one of sodium carboxymethyl cellulose, polyacrylic acid or sodium alginate,
[0030] The dispersant is selected from at least one of polyacrylamide and sodium lauryl sulfate,
[0031] The shear stirring has a rotation speed of 600 r / min to 1500 r / min and a time of 0.5 h to 1 h.
[0032] Furthermore, in step S2-1, the carbon fiber felt is selected from at least one of polyacrylonitrile-based carbon fiber felt, asphalt-based carbon fiber felt or viscose-based carbon fiber felt, and the thickness of the carbon fiber felt is 0.2 to 50 mm.
[0033] Furthermore, in steps S3, S4 and S5, the coupling agent is selected from at least one of KH550, KH560 and KH570, and the organosilane is selected from at least one of ethyl orthosilicate and methyl orthosilicate.
[0034] Furthermore, in step S4, the emissivity enhancing powder is selected from at least one of silicon carbide and aluminum oxide.
[0035] Furthermore, in step S5, the conductive enhancing powder is selected from at least one of titanium carbide and zirconium boride.
[0036] Furthermore, in step S6-1, the silicon oxide precursor is selected from at least one of ethyl silicate or methyl silicate, the aluminum oxide precursor is aluminum isopropoxide, and the titanium oxide precursor is selected from at least one of titanium tetrachloride or tetrabutyl titanate.
[0037] Furthermore, in step S7-2, the alkali metal carbonate aqueous solution is selected from at least one of a lithium carbonate aqueous solution, a sodium carbonate aqueous solution or a potassium carbonate aqueous solution.
[0038] On the other hand, the present invention also provides a high temperature resistant carbon fiber electric heating felt prepared by the above preparation method.
[0039] In the third aspect, the present invention also provides the application of the high temperature resistant carbon fiber electric heating felt prepared above in the field of electric heating. The obtained carbon fiber electric heating felt with enhanced high temperature resistance based on double-layer coating has an initial oxidation temperature of >650°C while maintaining the original light weight, flexibility, stable conductive properties and high emissivity, raising the upper limit of electric heating application temperature to 600°C, significantly expanding its application range in the field of electric heating, and can be applied to electric heating application scenarios with an upper temperature limit of around 600°C, such as industrial heating, special material processing, high temperature experimental equipment, etc., with good application prospects and economic benefits.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] (1) Resistant to high temperature oxidation and applicable to high temperature electric heating applications: The present invention provides a high temperature resistant carbon fiber electric heating felt that can withstand a high temperature of 600°C, and its carbon fiber does not oxidize and is stably conductive. This is because the surface of the carbon fiber has been subjected to high temperature heat treatment and is pre-coated with a layer of nano-lining layer. The nano-lining layer forms a strong Si-C bond and Ti-C bond with the surface of the carbon fiber, changing the originally smooth and inert carbon fiber surface into a rough and active nano-lining, which is conducive to the uniform adhesion of the subsequent coating; at the same time, the subsequent long-term impregnation process allows nanoparticles such as silicon carbide, aluminum oxide, titanium carbide, and zirconium boride to be uniformly self-assembled on the surface of the carbon fiber coated with the nano-lining, which not only ensures the uniform coating of the coating, but also avoids the generation of excess sol bonding between the fibers. In addition, the periodic addition of an alkali metal carbonate aqueous solution can introduce alkali metal elements into the coating as a flux, allowing the nano-coating to be densified during the subsequent heat treatment process. In summary, the modification of the nano lining layer, the promotion of the self-assembly process, and the introduction of alkali metal elements enable the outer coating to evenly cover the surface of each carbon fiber and densely isolate oxygen, providing a structural basis for the use of carbon fiber electric heating felt at high temperatures of 600°C.
[0042] (2) High emissivity and good conductivity: The present invention provides a high-temperature resistant carbon fiber electric heating felt, which is characterized in that nanoparticles such as silicon carbide, aluminum oxide, titanium carbide, and zirconium boride in the mixed sol are self-assembled on the surface of the carbon fiber to form an outer coating, and the unique properties of these nanoparticles are fully utilized to effectively ensure the overall conductivity and radiation characteristics of the carbon fiber electric heating felt. First, silicon carbide and aluminum oxide with high infrared radiation emissivity are selected as emissivity enhancement powders to weaken the negative impact of the dense coating itself on the infrared emissivity of the carbon fiber felt; then, conductive nanopowders such as titanium carbide and zirconium boride are added as conductive enhancement powders to construct a conductive network in the dense coating to ensure the overall high conductivity of the carbon fiber electric heating felt. In addition, silanization treatment is performed on the surface of the nanoparticles and the carbon fiber to improve the interface bonding between them, so that the nanoparticles can form a uniform and stable self-assembled nano coating on the surface of the carbon fiber. Finally, the densification of the coating provides good coating and fixation for the emissivity enhancement powder and the conductivity enhancement powder. The synergistic effect of these mechanisms enables the carbon fiber electric heating felt to maintain stable conductive properties and high emissivity under the coverage of dense coating.
[0043] (3) Lightweight and flexible: The present invention provides a carbon fiber electric heating felt with enhanced high temperature resistance based on a double-layer coating, which retains the lightness and flexibility of the original carbon fiber electric heating felt after coating. First, in the preparation process, inorganic powders below 100nm are mainly used. Through the self-assembly process, nanoparticles can be evenly and stably attached to the surface of carbon fiber, avoiding local excessive aggregation or accumulation. The thickness of the coating can be effectively controlled, and the thickest position does not exceed 0.5 microns. This thinner coating structure will not have a significant impact on the intrinsic lightness and flexibility of the carbon fiber electric heating felt. In addition, during the composite sol reaction process, by periodically adding an alkali metal carbonate aqueous solution, the pH value of the coating can be adjusted, the condensation reaction of the oxide gel can be promoted, the density and continuity of the coating can be further optimized, and the uniformity of the coating can be ensured. In summary, by finely controlling the size and dispersion of nanoparticles and optimizing the thickness and uniformity of the coating, the carbon fiber electric heating felt can maintain its original lightness and flexibility while meeting the requirements of high temperature environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Thermogravimetric test results of different carbon fiber electric heating felt samples;
[0045] Figure 2 The weight loss rate of different carbon fiber electric heating felt samples when kept at 600℃ for 10min;
[0046] Figure 3 This is a SEM photo of the nanocomposite lining layer of the high temperature resistant carbon fiber electric heating felt sample of Example 1 of the present invention;
[0047] Figure 4 This is a SEM photo of a double-layer dense coating on the surface of a high-temperature resistant carbon fiber electric heating felt sample according to Example 1 of the present invention;
[0048] Figure 5 is the normal spectral emissivity of the original carbon fiber electric heating felt without any treatment;
[0049] Figure 6 is the normal spectral emissivity of the high temperature resistant carbon fiber electric heating felt sample of Example 1 of the present invention;
[0050] Figure 7 is the normal spectral emissivity of the high temperature resistant carbon fiber electric heating felt sample of Example 2 of the present invention;
[0051] Figure 8 is the normal spectral emissivity of the high temperature resistant carbon fiber electric heating felt sample of Example 3 of the present invention;
[0052] Fig. 9 The electric heating curves of different carbon fiber electric heating felt samples (input power 100W);
[0053] Fig.10 is the resistivity of different carbon fiber electric heating felt samples;
[0054] Fig.11 This is a photograph of the flexible bending of the high temperature resistant carbon fiber electric heating felt sample of Example 1 of the present invention. DETAILED DESCRIPTION
[0055] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0056] The present invention provides a method for preparing a high temperature resistant carbon fiber electric heating felt, comprising the following steps:
[0057] S1, mixing silicon oxide, titanium oxide, silicon carbide, and titanium carbide nanopowders in a mass ratio of (0.5-2): (0.5-2): (0.5-2): (0.5-2) by ball milling at a speed of 200 r / min-500 r / min for 0.5 h-3 h to obtain a mixed nanopowder, then adding water, a coupling agent, a thickener, and a dispersant, and shearing and stirring at a speed of 600 r / min-1500 r / min for 0.5 h-1 h to obtain a nanocomposite emulsion, wherein the particle size range of the silicon oxide, titanium oxide, silicon carbide, and titanium carbide nanopowders is 20nm~80nm, the mass ratio of water to mixed nano powder is 1:1~3:1, the mass of coupling agent is 1~5% of the total mass of water and mixed nano powder, the mass of thickener is 5~15% of the total mass of water and mixed nano powder, the mass of dispersant is 1~3% of the total mass of water and mixed nano powder, the coupling agent is selected from at least one of KH550, KH560 or KH570, the thickener is selected from at least one of sodium carboxymethyl cellulose, polyacrylic acid or sodium alginate, and the dispersant is selected from at least one of polyacrylamide or sodium dodecyl sulfate;
[0058] S2, Preparation of Carbon Fiber Felt Nanocomposite Lining Layer:
[0059] S2-1, immersing the carbon fiber felt in concentrated nitric acid at 75° C. for oxidation activation for 3 to 8 hours, washing with water and then drying to obtain an activated carbon fiber felt, wherein the carbon fiber felt is selected from at least one of polyacrylonitrile-based carbon fiber felt, asphalt-based carbon fiber felt or viscose-based carbon fiber felt, and the thickness of the carbon fiber felt is 0.2 to 50 mm;
[0060] S2-2, immersing the activated carbon fiber felt obtained in step S2-1 into the nanocomposite emulsion obtained in step S1, heating to 50-60° C., and ultrasonically treating for 30 min with an ultrasonic power of 50-100 W and a frequency of 20-60 kHz;
[0061] S2-3, taking out the carbon fiber felt treated in step S2-2, drying it at 60-80° C. for 1-3 hours, and then performing heat treatment, wherein the heat treatment conditions are: nitrogen atmosphere, heating rate of 3-5° C. / min, heating to 1300-1600° C., keeping the temperature for 2-3 hours, and cooling naturally;
[0062] S2-4, heating the carbon fiber felt treated in step S2-3 to 50-60° C., and ultrasonically cleaning the felt for 0.5-3 h at an ultrasonic power of 80-120 W and a frequency of 30-80 kHz to obtain a carbon fiber felt with a nano-composite lining layer coated on the fiber surface;
[0063] S3, silanization treatment of carbon fiber felt: immerse the carbon fiber felt with the nano-composite lining layer coated on the fiber surface obtained in step S2-4 in water, then add a coupling agent with a mass of 1 to 3% of the mass of water and an organic silane with a mass of 1 to 3% of the mass of water, stir well and let stand for 20 to 30 hours, take out, dry, and obtain a carbon fiber felt with silanized fiber surface;
[0064] S4, silanization treatment of the emissivity enhancing powder: fully stir water, emissivity enhancing powder, coupling agent, and organic silane in a mass ratio of 100:(5-15):(1-3):(1-3), let stand for 20-30 hours, take out, and dry to obtain silanized emissivity enhancing powder;
[0065] S5, silanization treatment of the conductive enhanced powder: fully stir water, conductive enhanced powder, coupling agent, and organic silane in a mass ratio of 100:(5-15):(1-3):(1-3), let stand for 20-30 hours, take out, and dry to obtain silanized conductive enhanced powder;
[0066] In some specific embodiments, in steps S3, S4, and S5, the coupling agent is selected from at least one of KH550, KH560, or KH570, and the organosilane is selected from at least one of ethyl orthosilicate or methyl orthosilicate;
[0067] In some specific embodiments, in step S4, the emissivity enhancing powder is selected from at least one of silicon carbide or aluminum oxide;
[0068] In some specific embodiments, in step S5, the conductive enhancement powder is selected from at least one of titanium carbide and zirconium boride;
[0069] S6, preparation of silicon oxide-aluminum oxide-titania composite sol:
[0070] S6-1, uniformly mixing a silicon oxide precursor, an aluminum oxide precursor, and a titanium oxide precursor in a molar ratio of (2-3): (1-1.5): (1-1.5), then adding anhydrous ethanol in a ratio of anhydrous ethanol volume: total volume of precursors = (2:1)-(3:1), and mixing thoroughly to obtain a precursor mixed solution, wherein the silicon oxide precursor is selected from at least one of ethyl silicate or methyl silicate, the aluminum oxide precursor is aluminum isopropoxide, and the titanium oxide precursor is selected from at least one of titanium tetrachloride or tetrabutyl titanate;
[0071] S6-2, slowly adding water dropwise to the precursor mixed solution obtained in step S6-1 while stirring, wherein the molar ratio of the total amount of the precursor to the added water is 3:1 to 4:1;
[0072] S6-3, adjusting the pH of the solution obtained in step S6-2 to 5-6 with glacial acetic acid, aging at room temperature to 60° C. for 20-30 hours to obtain a silicon oxide-aluminum oxide-titanium oxide composite sol;
[0073] S7, outer coating self-assembly step:
[0074] S7-1, dispersing the silanized emissivity enhancement powder obtained in step S4 and the silanized conductivity enhancement powder obtained in step S5 in the silicon oxide-alumina-titania composite sol obtained in step S6-3, wherein the mass ratio of the silanized emissivity enhancement powder, the silanized conductivity enhancement powder, and the silicon oxide-alumina-titania composite sol is (2-5):1:(3-10), and after sufficient stirring, adding the carbon fiber felt with silanized fiber surface obtained in step S3, and reacting for 1-3 days under slow stirring;
[0075] S7-2, during the reaction process, 5 g of a 3-5 wt.% aqueous solution of an alkali metal carbonate is added dropwise every 6-8 hours, wherein the aqueous solution of the alkali metal carbonate is selected from at least one of an aqueous solution of lithium carbonate, an aqueous solution of sodium carbonate or an aqueous solution of potassium carbonate. After the reaction is completed, the pH of the reaction system is adjusted to 8-12 with 5-20 wt.% aqueous ammonia, and then the carbon fiber felt is taken out, rinsed 1-2 times with anhydrous ethanol, and dried at 60-80° C. for 2 hours to obtain a carbon fiber felt with a surface self-assembled outer layer coating;
[0076] S8, densification of the self-assembled outer layer coating: heat-treat the carbon fiber felt with the surface self-assembled outer layer coating obtained in step S7-2 under the following conditions: nitrogen atmosphere, heating to 800-1200°C at 3-10°C / min, keeping warm for 1-3h, and naturally cooling to obtain a high-temperature resistant carbon fiber electric heating felt with a double-layer coating on the fiber surface.
[0077] A high-temperature resistant carbon fiber electric heating felt is prepared by the preparation method, and the high-temperature resistant performance of the carbon fiber electric heating felt is enhanced based on a double-layer coating.
[0078] The high temperature resistant carbon fiber electric heating felt prepared above can be used in the electric heating field. The high temperature resistant carbon fiber electric heating felt prepared, while maintaining the original light weight, flexibility, stable conductive properties and high emissivity, has an initial oxidation temperature > 650°C, raising the upper limit of electric heating application temperature to 600°C, significantly expanding its application range in the electric heating field, and can be applied to electric heating application scenarios with a temperature upper limit of around 600°C, such as industrial heating, special material processing, high temperature experimental equipment, etc., with good application prospects and economic benefits.
[0079] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0080] Example 1
[0081] A method for preparing a high temperature resistant carbon fiber electric heating felt is as follows:
[0082] S1, weigh 2.5g of silicon oxide, 5g of titanium oxide, 6g of silicon carbide, and 8g of titanium carbide nanopowders, mix them by ball milling at a speed of 200r / min for 0.5h to obtain mixed nanopowders, then add water, KH550, sodium carboxymethyl cellulose, and polyacrylamide, and shear and stir them at a speed of 600r / min for 0.5h to obtain a nanocomposite emulsion, wherein the particle size of the silicon oxide, titanium oxide, silicon carbide, and titanium carbide nanopowders is 20nm, the mass ratio of water to the mixed nanopowder is 1:1, the mass of KH550 is 1% of the total mass of the water and the mixed nanopowders, the mass of sodium carboxymethyl cellulose is 5% of the total mass of the water and the mixed nanopowders, and the mass of polyacrylamide is 1% of the total mass of the water and the mixed nanopowders;
[0083] S2, preparation of polyacrylonitrile-based carbon fiber felt nanocomposite lining layer:
[0084] S2-1, immersing a polyacrylonitrile-based carbon fiber felt having a thickness of 0.2 mm in concentrated nitric acid at 75° C. for oxidation activation for 3 h, washing with water and then drying to obtain an activated polyacrylonitrile-based carbon fiber felt;
[0085] S2-2, immersing the activated polyacrylonitrile-based carbon fiber felt obtained in step S2-1 into the nanocomposite emulsion obtained in step S1, heating to 50° C., and ultrasonically treating for 30 min at an ultrasonic power of 50 W and a frequency of 30 kHz;
[0086] S2-3, taking out the polyacrylonitrile-based carbon fiber felt treated in step S2-2, drying it at 60° C. for 3 h, and then performing a heat treatment, wherein the heat treatment conditions are: nitrogen atmosphere, heating rate of 3° C. / min, heating to 1300° C., keeping the temperature for 2 h, and cooling naturally;
[0087] S2-4, heating the polyacrylonitrile-based carbon fiber felt treated in step S2-3 to 50° C., and ultrasonically cleaning the felt for 0.5 h at an ultrasonic power of 80 W and a frequency of 60 kHz to remove excess inorganic powder in the pores of the carbon fiber felt, thereby obtaining a polyacrylonitrile-based carbon fiber felt with a nanocomposite lining layer coated on the fiber surface;
[0088] S3, silanization treatment of polyacrylonitrile-based carbon fiber felt: immerse the polyacrylonitrile-based carbon fiber felt with a nano-composite lining layer coated on the fiber surface obtained in step S2-4 in 100 mL of water, and then add KH550 with a mass of 1.5% of the mass of water and ethyl orthosilicate with a mass of 1.5% of the mass of water, stir well and let stand for 24 hours, take out, and dry to obtain the polyacrylonitrile-based carbon fiber felt with silanized fiber surface;
[0089] S4, silanization treatment of emissivity enhancing powder: 800g water, 40g emissivity enhancing powder (emissivity enhancing powder is 20g silicon carbide and 20g aluminum oxide), 12g KH550, and 12g tetraethyl orthosilicate are fully stirred and allowed to stand for 24h, taken out, and dried to obtain silanized emissivity enhancing powder, wherein the mass ratio of water, emissivity enhancing powder, KH550, and tetraethyl orthosilicate is 100:5:1.5:1.5;
[0090] S5, silanization treatment of conductive enhancing powder: 400g water, 20g conductive enhancing powder (the conductive enhancing powder is 10g titanium carbide and 10g zirconium boride), 6g KH550, and 6g tetraethyl orthosilicate are fully stirred and allowed to stand for 24h, taken out, and dried to obtain silanized conductive enhancing powder, wherein the mass ratio of water, conductive enhancing powder, KH550, and tetraethyl orthosilicate is 100:5:1.5:1.5;
[0091] S6, preparation of silicon oxide-aluminum oxide-titania composite sol:
[0092] S6-1, 0.2 mol of ethyl silicate, 0.1 mol of aluminum isopropoxide, and 0.1 mol of titanium tetrachloride are mixed evenly, and then anhydrous ethanol is added in a ratio of anhydrous ethanol volume: total volume of precursor (ethyl silicate + aluminum isopropoxide + titanium tetrachloride) = 2:1, and the mixture is fully mixed to obtain a precursor mixed solution;
[0093] S6-2, slowly adding water dropwise to the precursor mixed solution obtained in step S6-1 while stirring, wherein the molar ratio of the total amount of precursor (ethyl silicate+aluminum isopropoxide+titanium tetrachloride) to the added water is 3:1;
[0094] S6-3, adjusting the pH of the solution obtained in step S6-2 to 5 with glacial acetic acid, and aging at room temperature for 24 hours to obtain a silicon oxide-aluminum oxide-titania composite sol;
[0095] S7, outer coating self-assembly step:
[0096] S7-1, dispersing 40g of the silanized emissivity enhancing powder obtained in step S4 and 20g of the silanized conductivity enhancing powder obtained in step S5 in 60g of the silicon oxide-alumina-titania composite sol obtained in step S6-3, wherein the mass ratio of the silanized emissivity enhancing powder, the silanized conductivity enhancing powder, and the silicon oxide-alumina-titania composite sol is 2:1:3, and after sufficient stirring, adding the polyacrylonitrile-based carbon fiber felt with silanized fiber surface obtained in step S3, and reacting for 2 days under slow stirring;
[0097] S7-2, during the reaction process, 5 g of 3 wt.% lithium carbonate aqueous solution was added dropwise every 6 hours. After the reaction was completed, the pH of the reaction system was adjusted to 8 with 5 wt.% ammonia water, and then the polyacrylonitrile-based carbon fiber felt was taken out, rinsed twice with anhydrous ethanol to remove excess sol and powder in the pores of the carbon fiber felt, and then dried at 60° C. for 2 hours to obtain a polyacrylonitrile-based carbon fiber felt with a surface self-assembled outer layer coating;
[0098] S8, densification of the self-assembled outer coating: heat-treat the polyacrylonitrile-based carbon fiber felt with the surface self-assembled outer coating obtained in step S7-2 under the following conditions: nitrogen atmosphere, heating to 800°C at 3°C / min, keeping warm for 1h, and naturally cooling to obtain a high-temperature resistant polyacrylonitrile-based carbon fiber electric heating felt with a double-layer coating on the fiber surface.
[0099] Example 2
[0100] A method for preparing a high temperature resistant carbon fiber electric heating felt is as follows:
[0101] S1, weigh 3g of silicon oxide, 6g of titanium oxide, 2.5g of silicon carbide, and 2.5g of titanium carbide nanopowders, mix them by ball milling at a speed of 300r / min for 1h to obtain mixed nanopowders, then add water, KH560, polyacrylic acid, and sodium dodecyl sulfate, and shear and stir them at a speed of 800r / min for 0.8h to obtain a nanocomposite emulsion, wherein the particle size of silicon oxide, titanium oxide, silicon carbide, and titanium carbide nanopowders is 50nm, the mass ratio of water to mixed nanopowders is 2:1, the mass of KH560 is 3% of the total mass of water and mixed nanopowders, the mass of polyacrylic acid is 10% of the total mass of water and mixed nanopowders, and the mass of sodium dodecyl sulfate is 2% of the total mass of water and mixed nanopowders;
[0102] S2, preparation of polyacrylonitrile-based carbon fiber felt nanocomposite lining layer:
[0103] S2-1, immersing a polyacrylonitrile-based carbon fiber felt having a thickness of 20 mm in concentrated nitric acid at 75° C. for oxidation activation for 6 hours, washing with water and then drying to obtain an activated polyacrylonitrile-based carbon fiber felt;
[0104] S2-2, immersing the activated polyacrylonitrile-based carbon fiber felt obtained in step S2-1 into the nanocomposite emulsion obtained in step S1, heating to 55° C., and ultrasonically treating for 30 min at an ultrasonic power of 80 W and a frequency of 50 kHz;
[0105] S2-3, taking out the polyacrylonitrile-based carbon fiber felt treated in step S2-2, drying it at 70°C for 2h, and then performing a heat treatment, wherein the heat treatment conditions are: nitrogen atmosphere, heating rate of 4°C / min, heating to 1500°C, keeping the temperature for 2.5h, and cooling naturally;
[0106] S2-4, heating the polyacrylonitrile-based carbon fiber felt treated in step S2-3 to 55° C., and ultrasonically cleaning the felt for 2 hours at an ultrasonic power of 100 W and a frequency of 60 kHz to remove excess inorganic powder in the pores of the carbon fiber felt, thereby obtaining a polyacrylonitrile-based carbon fiber felt with a nanocomposite lining layer coated on the fiber surface;
[0107] S3, silanization treatment of polyacrylonitrile-based carbon fiber felt: immerse the polyacrylonitrile-based carbon fiber felt with a nano-composite lining layer coated on the fiber surface obtained in step S2-4 in 100 mL of water, and then add 2% of KH560 and 2% of methyl orthosilicate by weight of the water thereto, stir well and let stand for 24 hours, take out, and dry to obtain the polyacrylonitrile-based carbon fiber felt with silanized fiber surface;
[0108] S4, silanization treatment of emissivity enhancing powder: 400g water, 40g emissivity enhancing powder (emissivity enhancing powder is 20g silicon carbide and 20g aluminum oxide), 8g KH560, and 8g methyl orthosilicate are fully stirred and allowed to stand for 24h, taken out, and dried to obtain silanized emissivity enhancing powder, wherein the mass ratio of water, emissivity enhancing powder, KH560, and methyl orthosilicate is 100:10:2:2;
[0109] S5, silanization treatment of conductive enhancing powder: 200g water, 20g conductive enhancing powder (conductive enhancing powder is 10g titanium carbide and 10g zirconium boride), 5g KH560, and 5g methyl orthosilicate are fully stirred and allowed to stand for 24h, taken out, and dried to obtain silanized conductive enhancing powder, wherein the mass ratio of water, conductive enhancing powder, KH560, and methyl orthosilicate is 100:10:2.5:2.5;
[0110] S6, preparation of silicon oxide-aluminum oxide-titania composite sol:
[0111] S6-1, 0.25 mol of methyl silicate, 0.1 mol of aluminum isopropoxide, and 0.1 mol of titanium tetrachloride are uniformly mixed, and then anhydrous ethanol is added in a ratio of anhydrous ethanol volume: total volume of precursor (methyl silicate + aluminum isopropoxide + titanium tetrachloride) = 2.5:1, and the mixture is fully mixed to obtain a precursor mixed solution;
[0112] S6-2, slowly adding water dropwise to the precursor mixed solution obtained in step S6-1 while stirring, wherein the molar ratio of the total amount of precursor (methyl silicate+aluminum isopropoxide+titanium tetrachloride) to the added water is 3.5:1;
[0113] S6-3, adjusting the pH of the solution obtained in step S6-2 to 5.5 with glacial acetic acid, aging at 40° C. for 24 hours to obtain a silicon oxide-aluminum oxide-titania composite sol;
[0114] S7, outer coating self-assembly step:
[0115] S7-1, dispersing 40g of the silanized emissivity enhancing powder obtained in step S4 and 10g of the silanized conductivity enhancing powder obtained in step S5 in 50g of the silicon oxide-alumina-titania composite sol obtained in step S6-3, wherein the mass ratio of the silanized emissivity enhancing powder, the silanized conductivity enhancing powder, and the silicon oxide-alumina-titania composite sol is 4:1:5, and after sufficient stirring, adding the polyacrylonitrile-based carbon fiber felt with silanized fiber surface obtained in step S3, and reacting for 2 days under slow stirring;
[0116] S7-2, during the reaction process, 5 g of 4 wt.% sodium carbonate aqueous solution was added dropwise every 7 hours. After the reaction was completed, the pH of the reaction system was adjusted to 10 with 12 wt.% ammonia water, and then the polyacrylonitrile-based carbon fiber felt was taken out, rinsed twice with anhydrous ethanol to remove excess sol and powder in the pores of the carbon fiber felt, and then dried at 70°C for 2 hours to obtain a polyacrylonitrile-based carbon fiber felt with a surface self-assembled outer layer coating;
[0117] S8, densification of the self-assembled outer coating: heat-treat the polyacrylonitrile-based carbon fiber felt with the surface self-assembled outer coating obtained in step S7-2 under the following conditions: nitrogen atmosphere, heating to 1000°C at 5°C / min, keeping warm for 2h, and naturally cooling to obtain a high-temperature resistant polyacrylonitrile-based carbon fiber electric heating felt with a double-layer coating on the fiber surface.
[0118] Example 3
[0119] A method for preparing a high temperature resistant carbon fiber electric heating felt is as follows:
[0120] S1, weigh 5g of silicon oxide, 3.5g of titanium oxide, 6g of silicon carbide, and 8g of titanium carbide nanopowder, mix them by ball milling at a speed of 500r / min for 3h to obtain mixed nanopowder, then add water, KH570, sodium alginate, and sodium dodecyl sulfate, and shear and stir them at a speed of 1400r / min for 1h to obtain a nanocomposite emulsion, wherein the particle size of silicon oxide, titanium oxide, silicon carbide, and titanium carbide nanopowder is 80nm, the mass ratio of water to mixed nanopowder is 3:1, the mass of KH570 is 5% of the total mass of water and mixed nanopowder, the mass of sodium alginate is 15% of the total mass of water and mixed nanopowder, and the mass of sodium dodecyl sulfate is 3% of the total mass of water and mixed nanopowder;
[0121] S2, preparation of polyacrylonitrile-based carbon fiber felt nanocomposite lining layer:
[0122] S2-1, immersing a polyacrylonitrile-based carbon fiber felt having a thickness of 50 mm in concentrated nitric acid at 75° C. for oxidation activation for 8 hours, washing with water and then drying to obtain an activated polyacrylonitrile-based carbon fiber felt;
[0123] S2-2, immersing the activated polyacrylonitrile-based carbon fiber felt obtained in step S2-1 into the nanocomposite emulsion obtained in step S1, heating to 60° C., and ultrasonically treating for 30 min, with an ultrasonic power of 100 W and a frequency of 60 kHz;
[0124] S2-3, taking out the polyacrylonitrile-based carbon fiber felt treated in step S2-2, drying it at 80°C for 3 hours, and then performing a heat treatment. The heat treatment conditions are: nitrogen atmosphere, heating rate of 5°C / min, heating to 1600°C, keeping the temperature for 3 hours, and cooling naturally;
[0125] S2-4, heating the polyacrylonitrile-based carbon fiber felt treated in step S2-3 to 60° C., and ultrasonically cleaning the felt for 3 hours at an ultrasonic power of 120 W and a frequency of 80 kHz to remove excess inorganic powder in the pores of the carbon fiber felt, thereby obtaining a polyacrylonitrile-based carbon fiber felt with a nanocomposite lining layer coated on the fiber surface;
[0126] S3, silanization treatment of polyacrylonitrile-based carbon fiber felt: immerse the polyacrylonitrile-based carbon fiber felt with a nano-composite lining layer coated on the fiber surface obtained in step S2-4 in 100 mL of water, and then add 3% of KH570 and 3% of methyl orthosilicate by weight of the water thereto, stir well and let stand for 24 hours, take out, and dry to obtain the polyacrylonitrile-based carbon fiber felt with silanized fiber surface;
[0127] S4, silanization treatment of emissivity enhancing powder: 400g water, 60g emissivity enhancing powder (emissivity enhancing powder is 30g silicon carbide and 30g aluminum oxide), 12g KH570, and 12g methyl orthosilicate are fully stirred and allowed to stand for 24h, taken out, and dried to obtain silanized emissivity enhancing powder, wherein the mass ratio of water, emissivity enhancing powder, KH570, and methyl orthosilicate is 100:15:3:3;
[0128] S5, silanization treatment of conductive enhancing powder: 200g water, 30g conductive enhancing powder (conductive enhancing powder is 15g titanium carbide and zirconium boride), 6g KH570, and 6g methyl orthosilicate are fully stirred and allowed to stand for 24h, taken out, and dried to obtain silanized conductive enhancing powder, wherein the mass ratio of water, conductive enhancing powder, KH570, and methyl orthosilicate is 100:15:3:3;
[0129] S6, preparation of silicon oxide-aluminum oxide-titania composite sol:
[0130] S6-1, 0.3 mol of ethyl silicate, 0.15 mol of aluminum isopropoxide, and 0.1 mol of tetrabutyl titanate are mixed evenly, and then anhydrous ethanol is added in a ratio of anhydrous ethanol volume: total volume of precursor (ethyl silicate + aluminum isopropoxide + tetrabutyl titanate) = 3:1, and the mixture is fully mixed to obtain a precursor mixed solution;
[0131] S6-2, slowly adding water dropwise to the precursor mixed solution obtained in step S6-1 while stirring, wherein the molar ratio of the total amount of precursor (ethyl silicate+aluminum isopropoxide+tetrabutyl titanate) to the added water is 4:1;
[0132] S6-3, adjusting the pH of the solution obtained in step S6-2 to 6 with glacial acetic acid, aging at 60° C. for 24 hours to obtain a silicon oxide-aluminum oxide-titania composite sol;
[0133] S7, outer coating self-assembly step:
[0134] S7-1, dispersing 50g of the silanized emissivity enhancing powder obtained in step S4 and 10g of the silanized conductivity enhancing powder obtained in step S5 in 100g of the silicon oxide-alumina-titania composite sol obtained in step S6-3, wherein the mass ratio of the silanized emissivity enhancing powder, the silanized conductivity enhancing powder, and the silicon oxide-alumina-titania composite sol is 5:1:10, and after fully stirring, adding the polyacrylonitrile-based carbon fiber felt with silanized fiber surface obtained in step S3, and reacting for 3 days under slow stirring;
[0135] S7-2, during the reaction process, 5 g of 4 wt.% potassium carbonate aqueous solution was added dropwise every 8 hours. After the reaction was completed, the pH of the reaction system was adjusted to 12 with 15 wt.% ammonia water, and then the polyacrylonitrile-based carbon fiber felt was taken out, rinsed twice with anhydrous ethanol to remove excess sol and powder in the pores of the carbon fiber felt, and then dried at 80° C. for 2 hours to obtain a polyacrylonitrile-based carbon fiber felt with a self-assembled outer layer coating on the surface;
[0136] S8, densification of the self-assembled outer coating: heat-treat the polyacrylonitrile-based carbon fiber felt with the surface self-assembled outer coating obtained in step S7-2 under the following conditions: nitrogen atmosphere, heating to 1200°C at 10°C / min, keeping warm for 3h, and naturally cooling to obtain a high-temperature resistant polyacrylonitrile-based carbon fiber electric heating felt with a double-layer coating on the fiber surface.
[0137] Comparative Example 1
[0138] This comparative example is commercially available polyacrylonitrile-based carbon fiber felt that has not been treated in any way.
[0139] The carbon fiber felt samples of the above embodiments and comparative examples were characterized as follows:
[0140] (1) Thermogravimetric Analysis (TGA) is a thermal analysis technique that measures the weight change of a sample at elevated or constant temperature to investigate its thermal, chemical, and structural properties. The principle is based on the mass change of a sample at elevated or constant temperature, and can analyze reactions such as thermal decomposition, desorption, and oxidation of the sample.
[0141] Test conditions:
[0142] Test 1: Air atmosphere, 20°C / min, room temperature to 800°C.
[0143] Test 2: Air atmosphere, 20℃ / min, 600℃ for 10min.
[0144] (2) Characterization of coating micromorphology: The coating micromorphology was analyzed using a FlexSEM 1000 scanning electron microscope.
[0145] (3) Normal spectral emissivity test: The thermal radiation performance is measured using an automatic spectroscopic radiation test system.
[0146] (4) Electric heating performance test:
[0147] The experimental device includes: an electric heating element, an electrode, a conductive circuit and an input power supply. The test uses the carbon fiber electric heating felt with enhanced high temperature resistance prepared by the present invention as the electric heating element, uses a conductive copper foil strip as the electrode material, and uses an adjustable voltage DC power supply for power supply.
[0148] A K-type thermocouple is used for real-time temperature testing.
[0149] The test process includes three stages: heating process, constant temperature process, and power-off cooling process.
[0150] (5) Resistivity test
[0151] Required equipment: DC regulated power supply, digital multimeter or voltmeter, ammeter or current probe and sample fixture (for fixing carbon fiber felt sample).
[0152] Measurement steps:
[0153] 1. Sample preparation: Cut samples of a certain size from the carbon fiber felt, measure and record the length (L), width (W) and thickness (T) of the sample.
[0154] 2. Sample installation: Fix the sample on the sample fixture to ensure good electrode contact.
[0155] 3. Current-voltage measurement:
[0156] a. Use a DC regulated power supply to apply a constant current (I) to the sample.
[0157] b. Use a digital multimeter or voltmeter to measure the voltage (V) across the sample.
[0158] 4. Resistance calculation: Calculate the resistance (R) of the sample according to Ohm's law: R = V / I.
[0159] 5. Resistivity calculation: According to the geometric dimensions of the sample, calculate the resistivity (ρ) of the sample: ρ = R × A / L, where A is the cross-sectional area of the sample (A = W × T).
[0160] The above characterization results are as follows:
[0161] like Figure 1 , Figure 2 As shown, the weight loss rates of the high temperature resistant carbon fiber electric heating felt samples prepared by the formula and process in Example 1, Example 2 or Example 3 of the present invention after being kept at 600°C for 10 minutes were 0.16%, 0.21% and 0.22% respectively, which were significantly lower than the weight loss rate of the carbon fiber electric heating felt sample without any treatment in Comparative Example 1, which was 35%. Figure 1 , Fig. 9 As shown, after the carbon fiber electric heating felt sample of comparative example 1 of the present invention is quickly heated to 550°C without any treatment, the material is oxidized, the structure is destroyed, the performance is unstable, and the temperature drops sharply; on the contrary, the initial oxidation temperature of the high temperature resistant carbon fiber electric heating felt sample prepared by the formula and process in Example 1, Example 2 or Example 3 is increased by 150-200°C, and it can generate heat stably between 600-650°C, indicating that the high temperature resistant carbon fiber felt sample of the present invention can withstand a high temperature of 600°C, and its carbon fiber is modified by the nano-lining layer, the self-assembly process is promoted, and the alkali metal elements are introduced, so that the outer coating can be evenly coated on the surface of each carbon fiber, densely oxygen-isolated, and the carbon fiber is not oxidized, providing a structural basis for the use of the carbon fiber electric heating felt at a high temperature of 600°C. The above results show that the high temperature resistant carbon fiber electric heating felt of the present invention can be widely used in various electric heating scenarios requiring a temperature upper limit of 600°C, such as industrial heating, special material processing, high temperature experimental equipment, etc., providing a new solution for high temperature electric heating applications.
[0162] like Figure 3 As shown, the nanocomposite lining layer of the high temperature resistant carbon fiber electric heating felt sample of Example 1 of the present invention is stably coated on the carbon fiber surface, changing the originally smooth and inert carbon fiber surface into a rough and active nano lining, which is beneficial to the uniform adhesion of subsequent coatings.
[0163] like Figure 4 As shown, the carbon fiber surface of the high temperature resistant carbon fiber electric heating felt sample of Example 1 of the present invention is evenly coated with a double-layer coating, which is densely oxygen-isolated and provides a structural basis for the use of the carbon fiber electric heating felt at a high temperature of 600°C.
[0164] like Figure 5-8 As shown, the high temperature resistant carbon fiber electric heating felt samples prepared by the formula and process in Example 1, Example 2 or Example 3 have higher infrared emissivity, and the infrared emissivity is higher than 0.8. It can be seen that the high temperature resistant carbon fiber electric heating felt samples of Examples 1-3 self-assemble on the surface of carbon fiber to form an outer coating by selecting silicon carbide and aluminum oxide with high infrared radiation emissivity as emissivity enhancing powders. The densification of the coating provides good coating and fixation for the emissivity enhancing powder, weakening the negative impact of the dense coating on the infrared emissivity of the original carbon fiber felt, thereby maintaining the high emissivity of the original carbon fiber felt.
[0165] like Fig.10 As shown, the resistivity of the carbon fiber electric heating felt samples in Example 1, Example 2 or Example 3 of the present invention are 19.9mΩ·cm, 20.2mΩ·cm and 20.02mΩ·cm respectively, while the resistivity of the carbon fiber electric heating felt sample in Comparative Example 1 without any treatment is 20.1mΩ·cm, indicating that conductive nanopowders such as titanium carbide and zirconium boride are used as conductive reinforcing powders to build a conductive network in the dense coating. The densification of the coating provides good coating and fixation for the conductive reinforcing powder, ensuring the overall high conductive properties of the carbon fiber electric heating felt, so that the carbon fiber electric heating felt can still maintain stable conductive properties under the coating of the dense coating.
[0166] like Fig.11 As shown, the high temperature resistant carbon fiber electric heating felt sample of Example 1 of the present invention has good flexibility, and after being coated, it retains the light weight and flexibility characteristics of the original carbon fiber electric heating felt.
[0167] In summary, the preparation method of the high temperature resistant carbon fiber electric heating felt proposed in the present invention, while maintaining the original performance advantages of the carbon fiber electric heating felt, greatly improves the high temperature resistance, significantly expands its application field, and embodies good process stability and performance stability. The carbon fiber electric heating felt prepared in Examples 1, 2 and 3 of the present invention has stable process, reliable quality and excellent performance. Compared with the prior art, the high temperature resistant carbon fiber electric heating felt of the present invention, while maintaining the original light weight, flexibility, stable conductive properties and high emissivity, increases the upper limit of the electric heating application temperature to about 600°C, significantly expanding its application range in the electric heating field.
[0168] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a high temperature resistant carbon fiber electric heating felt, characterized in that: The following steps are involved: S1, mixing silicon oxide, titanium oxide, silicon carbide and titanium carbide nanopowders uniformly to obtain mixed nanopowders, then adding water, a coupling agent, a thickener and a dispersant, and obtaining a nanocomposite emulsion after shearing and stirring; S2, preparation of a carbon fiber felt nanocomposite lining layer: immersing the carbon fiber felt in concentrated nitric acid for oxidation activation, immersing the obtained activated carbon fiber felt in the nanocomposite emulsion prepared in step S1, and performing heat treatment to obtain a carbon fiber felt with a nanocomposite lining layer coated on the fiber surface; S3, silanization treatment of the carbon fiber felt: immersing the carbon fiber felt with the fiber surface coated with the nano-composite lining layer obtained in step S2 in water, then adding a coupling agent and an organic silane thereto, stirring thoroughly, leaving the mixture to stand, and drying to obtain a carbon fiber felt with the fiber surface silanized; S4, silanization treatment of the emissivity enhancing powder: water, emissivity enhancing powder, coupling agent, and organic silane are fully stirred, left to stand, and dried to obtain silanized emissivity enhancing powder; S5, silanization treatment of the conductive enhancing powder: fully stirring water, conductive enhancing powder, coupling agent, and organic silane, standing, and drying to obtain silanized conductive enhancing powder; S6, preparation of silicon oxide-aluminum oxide-titania composite sol: uniformly mix silicon oxide precursor, aluminum oxide precursor and titanium oxide precursor, add anhydrous ethanol, mix thoroughly to obtain a precursor mixed solution, add water to the precursor mixed solution and adjust the pH to 5-6, age and obtain silicon oxide-aluminum oxide-titania composite sol; S7, outer coating self-assembly step: the silanized emissivity enhancement powder obtained in step S4 and the silanized conductivity enhancement powder obtained in step S5 are dispersed in the silicon oxide-aluminum oxide-titanium oxide composite sol obtained in step S6, and after being fully stirred, the carbon fiber felt with silanized fiber surface obtained in step S3 is added thereto, and the reaction is carried out under slow stirring, and an alkali metal carbonate aqueous solution is added dropwise during the reaction process. After the reaction is completed, the pH of the reaction system is adjusted to 8-12, and then the carbon fiber felt is taken out, washed, and dried to obtain a carbon fiber felt with a surface self-assembled outer coating; S8, densification of the self-assembled outer layer coating: heat-treating the carbon fiber felt with the self-assembled outer layer coating on the surface obtained in step S7, and obtaining a high-temperature resistant carbon fiber electric heating felt with a double-layer coating on the fiber surface after natural cooling.
2. The method for preparing a high temperature resistant carbon fiber electric heating felt according to claim 1, characterized in that: In step S1, the mass ratio of silicon oxide, titanium oxide, silicon carbide and titanium carbide nanopowder is (0.5-2): (0.5-2): (0.5-2): (0.5-2); The mass ratio of water to mixed nanopowder is 1:1 to 3:1; The mass of the coupling agent is 1 to 5% of the total mass of water and the mixed nanopowder; The mass of the thickener is 5 to 15% of the total mass of the water and the mixed nano powder; The mass of the dispersant is 1-3% of the total mass of water and the mixed nano powder.
3. The method for preparing a high temperature resistant carbon fiber electric heating felt according to claim 1, characterized in that: In step S1, the particle size of the silicon oxide, titanium oxide, silicon carbide, and titanium carbide nanopowders is in the range of 20 nm to 80 nm; the coupling agent is selected from at least one of KH550, KH560, or KH570; the thickener is selected from at least one of sodium carboxymethyl cellulose, polyacrylic acid, or sodium alginate; and the dispersant is selected from at least one of polyacrylamide or sodium dodecyl sulfate.
4. The method for preparing a high temperature resistant carbon fiber electric heating felt according to claim 1, characterized in that: In step S2, the carbon fiber felt is selected from at least one of polyacrylonitrile-based carbon fiber felt, asphalt-based carbon fiber felt or viscose-based carbon fiber felt; and the thickness of the carbon fiber felt is 0.2 to 50 mm.
5. The method for preparing a high temperature resistant carbon fiber electric heating felt according to claim 1, characterized in that: In step S2, the heat treatment is specifically: heating and ultrasonic treatment in the nanocomposite emulsion, drying after taking out, heating to 1300-1600°C for heat treatment, and heating and ultrasonic cleaning after natural cooling.
6. The method for preparing a high temperature resistant carbon fiber electric heating felt according to claim 1, characterized in that: In steps S3, S4 and S5, the coupling agent is selected from at least one of KH550, KH560 and KH570, and the organosilane is selected from at least one of ethyl orthosilicate and methyl orthosilicate; In step S3, the mass of the coupling agent is 1-3% of the mass of water, and the mass of the organosilane is 1-3% of the mass of water; In step S4, the mass ratio of water, emissivity enhancing powder, coupling agent, and organosilane is 100:(5-15):(1-3):(1-3), and the emissivity enhancing powder is selected from at least one of silicon carbide and aluminum oxide; In step S5, the mass ratio of water, conductive enhancing powder, coupling agent and organosilane is 100:(5-15):(1-3):(1-3), and the conductive enhancing powder is selected from at least one of titanium carbide and zirconium boride.
7. The method for preparing a high temperature resistant carbon fiber electric heating felt according to claim 1, characterized in that: In step S6, the silicon oxide precursor is selected from at least one of ethyl silicate or methyl silicate; the aluminum oxide precursor is aluminum isopropoxide; the titanium oxide precursor is selected from at least one of titanium tetrachloride or tetrabutyl titanate; The molar ratio of the silicon oxide precursor, the aluminum oxide precursor and the titanium oxide precursor is (2-3): (1-1.5): (1-1.5).
8. The method for preparing a high temperature resistant carbon fiber electric heating felt according to claim 1, characterized in that: In step S7, the mass ratio of the silanized emissivity enhancing powder, the silanized conductivity enhancing powder, and the silicon oxide-aluminum oxide-titanium oxide composite sol is (2-5):1:(3-10); The alkali metal carbonate aqueous solution is selected from at least one of a lithium carbonate aqueous solution, a sodium carbonate aqueous solution or a potassium carbonate aqueous solution.
9. A high temperature resistant carbon fiber electric heating felt prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the high temperature resistant carbon fiber electric heating felt as claimed in claim 9 in the field of electric heating.
Citation Information
Patent Citations
A method for preparing high-temperature resistant, oxidation-resistant, and thermally conductive carbon fiber / silicon carbide composite material
CN105645962B
Preparation method of high temperature resistant and oxidation resistant carbon fiber
CN115262218B
Fiber-enhanced integrated material with high-temperature resistance property and high emissivity and preparation method thereof
CN108276015A
High-temperature resistant silica aerogel heat preservation felt preparation method
CN109574622A
Preparation method of carbon fiber surface modification anti-oxidation composite coating
CN110318253A